Update on the Health Services Research Doctoral Core Competencies. (13th March 2018) - Burgess, James F.; Menachemi, Nir; Maciejewski, Matthew L.
Abstract : Objective: To present revised core competencies for doctoral programs in health services research (HSR), modalities to deliver these competencies, and suggested methods for assessing mastery of these competencies. Data Sources and Data Collection: Core competencies were originally developed in 2005, updated (but unpublished) in 2008, modestly updated for a 2016 HSR workforce conference, and revised based on feedback from attendees. Additional feedback was obtained from doctoral program directors, employer/workforce experts and attendees of presentation on these competencies at the AcademyHealth's June 2017 Annual Research Meeting. Principal Findings: The current version (V2.1) competencies include the ethical conduct of research, conceptual models, development of research questions, study designs, data measurement and collection methods, statistical methods for analyzing data, professional collaboration, and knowledge dissemination. These competencies represent a core that defines what HSR researchers should master in order to address the complexities of microsystem to macro‐system research that HSR entails. There are opportunities to conduct formal evaluation of newer delivery modalities (e.g., flipped classrooms) and to integrate new Learning Health System Researcher Core Competencies, developed by AHRQ, into the HSR core competencies. Conclusions: Core competencies in HSR are a continually evolving work in progress because new research questions arise, new methods are developed, and the trans‐disciplinary nature of the field leads to new multidisciplinary and team building needs.